Long-run determinants of pollution: A robustness analysis - Michael J. Lamla (ETH Zurich, KOF Swiss Economic Institute, 2007)
This paper examines how robust economic, political, and demographic variables are related to water and air pollution. Employing Bayesian Averaging of Classical Estimates (BACE) for a cross section of up to 74 countries, 33 variables and 3 proxies for air and water pollution over a period from 1980 to 1995 we confirm the Environmental Kuznets Curve hypothesis, highlight the relevance of efficient production technologies and underline the role of political and demographic variables.
Keywords: C52; O13; Q53; 330; pollution; sensitivity analysis; BACE; Sozialer Indikator; Gewässerbelastung; Luftverunreinigung; Sensitivitätsanalyse; Welt